Anchoring in the Judgmental Evaluation of Audit Samples - Butler, Stephen A. (The Accounting Review, 1986)
[This study reports the results of two experiments designed to determine the anchor used by experienced auditors in their judgmental evaluation of a compliance test sample and a substantive test of details sample. Kinney and Uecker [1982] suggest that auditors use even odds as an anchor when evaluating compliance test samples. However, there are a number of other possible anchors. For instance, in a compliance test the auditor may also anchor on the tolerable error rate or an expectation of what will be found. The experiments reported in the following study discriminate among alternative explanations (anchors). The results indicate that there is anchoring behavior, but rather than showing that even odds or that a value stated in the problem is the anchor, it appears that experienced auditors make assessments of risk by starting from an "internal anchor" of five to ten percent.]